TYPES AND FORMS OF CONTINUING PROFESSIONAL DEVELOPMENT OF ACADEMIC STAFF (BY THE RESULTS OF THE POLL) - Bulvinska, Oksana; Bulvinsky, Maxim (Educological discourse, 2018)
The article is devoted to the results of the academic stuff of Ukrainian universities employees regarding to the types and forms of their professional development. Professional development forms are ordered according to their reducing degree in meaning for respondents by a ranking method. It was determined that the first three ranked places among the named types and forms of university lecturers professional development took such activities as studying at trainings, courses, coaching sessions outside the native educational institution; using online forms and self-analysing of own professional experience accordingly. Nationwide advanced training courses and a system of professional development within native higher education institutions are highly demanded among lecturers, although are clearly underdeveloped forms. According to the results of the study, it is suggested to cultivate types of professional growth of the academic stuff of higher education institutions at the expense of accredited educational programs in educational or scientific institutions; expanding of educational online resources of a Ukrainian Internet segment, as well as involvement of European and worldwide relevant resources. It is also perspective to develop the lecturers training system in the context of institutional autonomy as this is an all-European trend.